Scope and limitations of the dual-gold-catalysed hydrophenoxylation of alkynes - Gómez-Suárez, Adrián; Oonishi, Yoshihiro; Martin, Anthony R.; Nolan, Steven P. (Beilstein Journal of Organic Chemistry, 2016)
Due to the synthetic advantages presented by the dual-gold-catalysed hydrophenoxylation of alkynes, a thorough study of this reaction was carried out in order to fully define the scope and limitations of the methodology. The protocol tolerates a wide range of functional groups, such as nitriles, ketones, esters, aldehydes, ketals, naphthyls, allyls or polyphenols, in a milder and more efficient manner than the previously reported methodologies. We have also identified that while we are able to use highly steric hindered phenols, small changes on the steric bulk of the alkynes have a dramatic effect on the reactivity. More importantly, we have observed that the use of substrates that facilitate the formation of diaurated species such as gem-diaurated or σ,π-digold–acetylide species, hinder the catalytic activity. Moreover, we have identified that the use of directing groups in unsymmetrical alkynes can help to achieve high regioselectivity in the hydrophenoxylation.
Keywords: cooperative catalysis; gold catalysis; hydrophenoxylation; N-heterocyclic carbene; vinyl ethers